PEMANFAATAN TEKNOLOGI SEBAGAI MEDIA PEMBELAJARAN KREATIF DI ERA 4.0 - Nena Puspita Sari; Afrida Hanum; Cut Maulina; Rini Susiani; Nurmalina Nurmalina (Universitas Pahlawan Tuanku Tambusai, 2022)
The use of technology is a demand that must be carried out in the 4.0 era. In the world of education, technology can be used as a medium of learning. This technology-based learning media can be developed according to the teacher's creativity. The teacher's role is very important in conveying knowledge and it will be easy if it is adjusted to the development of the 4.0 era, namely using technological media. SD Negeri Pertiwi Lambarot Aceh Besar District is one of the schools that want to implement this technology-based learning media. Therefore, the author carried out Community Service activities by giving seminars to all teachers at the school, totaling 25 teachers as activity participants. The methods used in these activities are lectures, discussions, and questions and answers. The results obtained from this activity are to add insight into the use of technology-based learning media and teachers begin to develop creative ideas to produce technology-based learning media which can then be implemented in the learning process at the school. Keywords: Era 4.0, Technology, Learning Media